Eksplorasi dan Eksploitasi Penambangan Emas Lebong Donok (Bengkulu) Tahun 1897-1942 - Rendi Andriyanto; Azmi Fitrisia (Jurnal Kronologi, 2019)
This study describe the Exploration and Exploitation gold mining in Lebong Donok, (Bengkulu) in 1897-1942. This research uses the historical method of the process: Heuristics, or data collection, then continued the procces of source criticism and interpretation of data, the final stage is the writing of history so that this research can be completed. The results showed that the first person to explore the Lebong Donok gold tambourine was Eugene Kassel. Eugene Kassel conducted a study in Lebong. The results of his research caught the attention of the owner of a mining company in Batavia so the company decided to explore the mine through Lebong Goud Syndicaat. The Dutch East Indies government granted management concessions to a Dutch private company named Mijnbouw Maatschappij Redjang Lebong in 1899 under the mining administrator H.J.A. Sanders, after the discovery of gold deposits at Lebong Donok in 1896 and the estabilishment of the company on 10 February 1897. The results of exploitation carried out by the Dutch East Indies government through private company Mijnbouw Maatschappij Redjang Lebong in Lebong Donok is very profitable and adds to the Dutch East Indies government.